2015
DOI: 10.1103/physrevd.92.085035
|View full text |Cite
|
Sign up to set email alerts
|

Lorentz violation correction to the Aharonov-Bohm scattering

Abstract: In this paper, using a (2+1)-dimensional field theory approach, we study the Aharonov-Bohm (AB) scattering with Lorentz symmetry breaking. We obtain the modified scattering amplitude to the AB effect due to the small Lorentz violation correction in the breaking parameter and prove that up to one loop the model is free from ultraviolet divergences. * Electronic address: anacleto@df.ufcg.edu.br

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Out of the broad framework of the SME, a nonminimal CPT-odd interaction between fermions and photons was proposed [23], with interesting consequences in the nonrelativistic limit of Dirac equation concerning topological effects and geometrical phases [24][25][26][27][28][29][30], Landau level [31] and on the high energy Bhabha cross section [32]. Similar types of CPT-odd nonminimal coupling were also investigated in the context of radiative generation evaluations [33][34][35], as well as fermion scattering at zero temperature [36] and at finite temperature [37].…”
Section: Introductionmentioning
confidence: 99%
“…Out of the broad framework of the SME, a nonminimal CPT-odd interaction between fermions and photons was proposed [23], with interesting consequences in the nonrelativistic limit of Dirac equation concerning topological effects and geometrical phases [24][25][26][27][28][29][30], Landau level [31] and on the high energy Bhabha cross section [32]. Similar types of CPT-odd nonminimal coupling were also investigated in the context of radiative generation evaluations [33][34][35], as well as fermion scattering at zero temperature [36] and at finite temperature [37].…”
Section: Introductionmentioning
confidence: 99%
“…The effect can also be simulated in quantum field theory as for example by using a nonrelativistic field theory for bosonic particles which interact with a Chern-Simons field [24]. More specifically, in [25] was addressed the AB effect considering the noncommutative spacetime and in [26] the effect was obtained due to violation of Lorentz symmetry in quantum field theory.…”
Section: Introductionmentioning
confidence: 99%
“…Once the pressure is generally a parameter that can be easily adjustable and it can represent the external field source, thus investigating the analogous Aharonov-Bohm (AB) effect due to a scattering of planar waves by an idealized draining bathtub vortex [66][67][68][69][70][71] is an interesting way of testing analog models via neo-Newtonian theory. As shown in [72], by analyzing the effect of AB it has been found that the phase change displays a dependence on the pressure and this has analogy with a magnetic flux.…”
mentioning
confidence: 99%